POTENTIAL STRATIGRAPHIC TRAPS ON PULUBALANG FORMATION INTERVAL, SANGATTA AREA, EAST KALIMANTAN - CITRA ADI , PERMANA
Sangatta field is one of the old oil field of PT PERTAMINA EP. (Otis & Schneidermann, 1997)Sangatta field has produced 313 MMSTB from Sangatta anticline structure with current daily production is around 1600 BOPD from 80 wells with the depth objective up to 1500 mbpl come through Formasi Balikpapan and achieved peak daily production around 9000 BOPD in 1990. Declining production at Sangatta field caused by the lack of exploration activity for the last ten years and has not developed the potential zone at Sangatta area. In 2011 Formasi Pulubalang has drilled three wells that come through the Formasi Pulubalang zone, and finally found hydrocarbon oil and gas.